2021
DOI: 10.1080/22221751.2021.2005453
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic and transmission analysis of Clostridioides difficile between environmental, animal, and clinical sources in China

Abstract: Clostridioides difficile is the most common pathogen causing antibiotic-associated diarrhea. Previous studies showed that diverse sources, aside from C. difficile infection (CDI) patients, played a major role in C. difficile hospital transmission. This study aimed to investigate relationships and transmission potential of C. difficile strains from different sources. A prospective study was conducted both in the intensive care unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
(67 reference statements)
2
13
0
Order By: Relevance
“…It is interesting to note that we found clade 4 and clade 5 strains with unusual STs (37, 35, 41, 48, 55, 95, and ST708) among Mexican isolates. Some of these STs have been isolated from different environmental, animal, and clinical sources (26) but are now circulating among humans and emerging as clinically important strains.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that we found clade 4 and clade 5 strains with unusual STs (37, 35, 41, 48, 55, 95, and ST708) among Mexican isolates. Some of these STs have been isolated from different environmental, animal, and clinical sources (26) but are now circulating among humans and emerging as clinically important strains.…”
Section: Discussionmentioning
confidence: 99%
“…In two instances (ST3-NT and ST15) we observed environmental and dog isolates differing by two or fewer SNPs. A study in China identified close genetic overlap with C. difficile isolates across all three reservoirs [42], although they used a core genome analysis with a distant outgroup and the effective core genome space was likely too small to clearly identify transmissions (see below). Although one study sampled the environment, pigs, and farmers within a single farm and failed to identify any zoonotic transmission [97], another study found genotypic overlap between isolates from humans and non-human animals [43].…”
Section: Discussionmentioning
confidence: 99%
“…This apparently near ubiquitous presence is likely due to the pathogen's ability to form oxygen resistant spores [34] and persist in a dormant state until a new mammalian host is found [37]. The potential transmission of C. difficile between animals and humans has been investigated [38][39][40][41][42], though direct transmission of C. difficile between animals and humans has only been rarely reported [43,44]. Although researchers have described C. difficile as omnipresent in humans, non-human animals, and the environment, a causal connection between environmental C. difficile isolates and human or animal disease is difficult to definitively demonstrate [17,41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, one of the dominant circulating RTs is RT017 [ 59 , 137 , 138 ]. However, another study published in 2021 on samples from different sources (e.g., soil, animals) found that the predominant RTs in China are RT001, RT046, and RT596 [ 139 ]. In 2021, the study by Zhao et al found that the most common clade in the Asian country is clade 4 [ 101 ].…”
Section: Worldwide Distribution Of C Difficile Rib...mentioning
confidence: 99%